Electrochemical Studies of Protonation Reaction of Anion Radicals of Some Dinitroaromatics in Dichloromethane - Hanif, Farzana; Yasmeen, Ghazala; Manzoor, Suryyia; Aamir, Muhammad (Asian Journal of Chemistry, 2015)
Protonation of anion radicals of 1,2-,1,3- and 1,4-dinitrobenzenes in dichloromethane in the temperature range 0, 5, 10 and 15 °C has been investigated by cyclic voltammetric method. Glassy carbon electrode and hanging mercury drop electrode are used as working electrodes. Benzoic acid and salicylic acid are used as protonating agents. Homogeneous rate constant is calculated by using Nicholson and Shain equation. The position of nucleophilic attack in dinitrobenzenes has been investigated by calculation of charge densities using MNDO and SCF-UHF molecular orbital methods. The heterogeneous rate constant ks,h for the first reduction process in dinitrobenzenes is determined by digital simulation of the cyclic voltammograms.